The work of the International Law Commission - United Nations (New York : United Nations, 2004)
This publication provides a general introduction to the work of the International Law Commission (ILC). It contains a brief historical outline of the various attempts at the development and codification of international law up to the inception of the ILC's work and an account of the organization, programme and methods of work of the ILC, with particular reference to the statute under which the ILC functions. The last part is devoted to brief descriptions of the various topics and sub-topics of international law considered by the General Assembly following the consideration of the topics and sub-topics by the ILC, and of the results achieved by diplomatic conferences convened by the General Assembly to consider drafts prepared by the ILC
"United Nations publication sales no. E.04.V.6"--Title page verso
Keywords: Commissie voor Internationaal Recht; Conventions internationales; International law; United Nations -- International Law Commission